'I chained him to protect him from the spirits.' What are the challenges for psychiatrists in India?. (November 2017) - Singh, Sukhmeet
Abstract : Approximately 20% of the adult Indian population are affected by a psychiatric disorder that requires intervention from a mental health professional (Math & Srinivasaraju, 2010). In spite of this, the provision of mental healthcare is poor. Therefore, to learn more, between July and August 2014 I undertook a 4-week elective at the Psychiatry Department of Sawai Man Singh (SMS) Hospital in Jaipur, Rajasthan, India. The Psychiatry Department was founded in 1952. It has a total of 332 beds, with nearly 20 000 patients admitted per year and an attendance of nearly 100 000 annually at the out-patient department.